Metformin Collaborates with PINK1/Mfn2 Overexpression to Prevent Cardiac Injury by Improving Mitochondrial Function - Zhuang Ma; Zuheng Liu; Xudong Li; Hao Zhang; Dunzheng Han; Wenjun Xiong; Haobin Zhou; Xi Yang; Qingchun Zeng; Hao Ren; Dingli Xu (Biology, 2023)
Both mitochondrial quality control and energy metabolism are critical in maintaining the physiological function of cardiomyocytes. When damaged mitochondria fail to be repaired, cardiomyocytes initiate a process referred to as mitophagy to clear defective mitochondria, and studies have shown that PTEN-induced putative kinase 1 (PINK1) plays an important role in this process. In addition, previous studies indicated that peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) is a transcriptional coactivator that promotes mitochondrial energy metabolism, and mitofusin 2 (Mfn2) promotes mitochondrial fusion, which is beneficial for cardiomyocytes. Thus, an integration strategy involving mitochondrial biogenesis and mitophagy might contribute to improved cardiomyocyte function. We studied the function of PINK1 in mitophagy in isoproterenol (Iso)-induced cardiomyocyte injury and transverse aortic constriction (TAC)-induced myocardial hypertrophy. Adenovirus vectors were used to induce PINK1/Mfn2 protein overexpression. Cardiomyocytes treated with isoproterenol (Iso) expressed high levels of PINK1 and low levels of Mfn2, and the changes were time dependent. PINK1 overexpression promoted mitophagy, attenuated the Iso-induced reduction in MMP, and reduced ROS production and the apoptotic rate. Cardiac-specific overexpression of PINK1 improved cardiac function, attenuated pressure overload-induced cardiac hypertrophy and fibrosis, and facilitated myocardial mitophagy in TAC mice. Moreover, metformin treatment and PINK1/Mfn2 overexpression reduced mitochondrial dysfunction by inhibiting ROS generation leading to an increase in both ATP production and mitochondrial membrane potential in Iso-induced cardiomyocyte injury. Our findings indicate that a combination strategy may help ameliorate myocardial injury by improving mitochondrial quality.